Myocardial dysfunction in patients with rheumatoid arthritis in the speckle-tracking echocardiography and its relationship with the clinical characteristics of the disease - Uzun , Kateryna; Batushkin , Valeriy; Gnylorybov Аndriy; Uzun , Dmytro; Krivosheya , Alina; Potapov, Yuriy (The Ukrainian Scientific Medical Youth Journal, 2024)
patients with RA have an approximately 50% increased risk of cardiovascular events and cardiovascular death. Cardiovascular diseases lead to a decrease in life expectancy, and the determination of the mechanisms of myocardial damage in patients with RA is of great importance for the development of methods for the early prevention of heart failure. The aim of our study was to study myocardial dysfunction using speckle tracking echocardiography (STE) in patients with RA and to find out possible correlations with the course of the disease and risk factors for cardiovascular diseases. Materials and methods. 29 RA patients were examined (5 in remission, 17.2%). Rheumatoid factor (RF), the level of antibodies to cyclic citrullinated peptides (a-CRP), quantitative C-reactive protein (CRP) was determined in the blood of all patients, and echocardiography and speckle-tracking echocardiography were performed to determine indicators of longitudinal deformation of the left ventricle. Disease activity was determined using the DAS28 index (CRP) and other functional and laboratory indicators. The results. The study of STE indicators is much better than "classical" echocardiography, revealing latent preclinical heart lesions. We established a significant decrease in Global Longitudinal Strain in the basal anterior and basal antero-septal segments (-17.24±3.01% and 15.94±9.37%, respectively) and preservation of local strain in the apical and middle segments (respectively -26.95+4.95% and -21.69+3.05%). In general, 41.2% of patients with RA had lesions of the basal segments. When analyzing the correlation between disease activity and deformation in STE, an inverse relationship between the DAS28 index and apical deformation (API Strain) was established (r=-0.50, р=0.06). The highest correlations were found between STE and functional status of disease: HAQ-DI score (r=-0.51, p=0.05) and VAS activity (r=-0.64, p=0.01). Conclusions. Functional activity according to the HAQ-DI score and VAS had a significantly greater relationship with preclinical manifestations of heart damage (detected by STE) than standard cardio-vascular risk factors. It is necessary to continue the search for other important factors that can lead to the formation of heart lesions and are related to both the activity of the disease and the functional status of patients. It is expedient to conduct comparative studies of STE in RA and coronary artery disease to clarify the differences in the processes of formation of myocardial damage.